Rincón de lectura y su incidencia del desarrollo de la imaginación en niños de educación inicial I - Vera Galarza, Lady Karina (2024)
The present research work teaches us the importance of an educational space in the classroom such as the reading corner, an important part of the imaginative development in early education children, this in turn promotes cognitive development. , linguistic and socio-emotional. It allows children to acquire new vocabulary, improve attention and concentration, develop creativity and strengthen emotional bonds. The main objective of the work will be to evaluate how the reading corner can improve the cognitive and imaginative capacity of students at the “Amarilis Sandoya Cepeda” Early Education Center, focusing on specific aspects such as vocabulary expansion, verbal comprehension, and expression. emotional. In addition, we will seek to understand how the introduction of a reading corner in the educational environment can stimulate the creativity and abstract thinking capacity of children aged 4 to 5 years, identifying possible improvements in their cognitive and emotional skills throughout the period. of evaluation. Based on a type of descriptive research because the main idea is to evaluate and at the same time detail the current effectiveness of the reading corner in the aforementioned Initial Education Center, having as population the teachers and parents of the students and applying a survey to each one of them. The results obtained support educational theories that emphasize the importance of providing environments rich in stimuli for the comprehensive development of students in the Initial Education stage. The connection between the introduction of reading corners and the increase in creativity, verbal comprehension and emotional expression highlights the relevance of this pedagogical practice as an effective tool to cultivate key skills in child development.